Biological control of Sclerotium rot of sunflower - R.D. PRASAD, R. RANGESHWARAN and (Indian Phytopathology, 2002)
Some 300 rhizosphere bacteria were tested for antagonism against Sclerotium rolfsii [Corticium rolfsii], the causal organism of root/collar rot in sunflower. A modified dual medium containing potato dextrose agar for pathogen growth and nutrient agar, Pseudomonas agar (for fluorescence) or tryptic soya agar for bacterial growth in the same plate was used to test for antagonism in dual culture. This dual medium method was most suitable to screen for antagonists in vitro. Eleven rhizobacteria antagonistic to S. rolfsii were identified which included Pseudomonas fluorescens (PDBCAB 1, 2, 15 and 26), Pseudomonas spp. (PDBCAB 7, 8, 15), P. putida (PDBCAB, 19), Streptomyces sp. (PDBCAB 23), Bacillus pantothenticus [Virgibacillus pantothenticus] (PDBCAB28) and Alcaligenes odorans (PDBCAB 12). Pseudomonas putida completely inhibited C. rolfsii under dual culture. All 11 isolates were tested for HCN production and four of the isolates showed positive reaction. One Pseudomonas sp. (PDBCAB 7), V. pantothenticus and A. odorans were antagonistic to C. rolfsii under dual cuture, but in pot culture percentages of disease-free plants were minimum (13-27%) for these three antagonists. Highest disease suppression was exhibited by P. fluorescens (PDBCAB 2) and P.putida (PDBCAB 19) (60-63% disease-free plants). The results indicate that selection of antagonistic bacteria must be based on greenhouse performance instead of relying on laboratory results.